Green Accounting Implementation on the Improvement of Company Financial Performance - Nuraini Sari; Tri Ayu Astari (Universitas Teknologi Yogyakarta, 2023)
Companies can minimize environmental problems by implementing green accounting. In addition, green accounting can also encourage company cost efficiency. This study aims to evaluate the implementation of Green Accounting on company financial performance. Manufacturing companies as a sector were chosen in this study because they are closely related to environmental issues. The sample was selected purposively from manufacturing companies and listed on the Indonesia Stock Exchange for the 2018-2020 period. The results of the study show that environmental performance has a positive influence on return on assets, environmental activity and environmental disclosure, which are indicators in green accounting that show an influence on a company's financial performance.